An Assessment of classroom Management Strategies and Students’ Academic achievement in Mathematics in Education vi, Lagos State - ONI, Leah Olubunmi; OWOLABI, Josiah (International Journal of Educational Management, 2025)
T his study was an assessment of classroom management strategies and students’ academic achievement in mathematics in Education District VI. The study adopted a descriptive research design and stratified random sampling techniques was u sed to select ten schools in the Education District VI of Lagos State while simple random sampling technique was adopted for the selection of forty students and two teachers in each school. The total sample size of 400 students and 20 teachers participated in the study. Two research questions and two hypotheses were raised, two instruments were used for collection of data, namely: Classroom Management Strategies (CMS) and Mathematics Achievement Test(MAT).The face and content validity of the instrument were done by the experts in Test Measurement and Evaluation. T he reliability coefficient value of CMS was found to be 0.7, it was therefore found to be reliable. The data collected was analyzed using descriptive statistics such as frequency counts, percentages, mean, standard deviation and inferential statistics such as Pearson Product Moment Correlation Coefficient analysis. The null hypotheses were tested at 0.05 significance level. The result from the study shows that weighted mean of 3.43 out of the maximum obtainable score of 4.00, which is higher than the standard mean of 2.50. T his signified that Mathematics teachers practice Teachers’ Reward System during Mathematics class. Also, the result reveals a low and negative linear relationship between those two variables (r =-.021); which was not statistically significant because p>0.05. Therefore, the null hypothesis was not rejected. The result implies that there is negative relationship between the two variables; that is, increase in classroom discipline during mathematics class has tendency of decreasing students’ achievement in Mathematics. It was therefore recommended that teachers should be conscious of the t ype of discipline they introduced during teaching and leamingrf Mathematics.